Sero-Prevalence and Genetic Diversity of Pandemic V. parahaemolyticus Strains Occurring at a Global Scale - Han, Chongxu; Tang, Hui; Ren, Chuanli; Zhu, Xiaoping; Han, Dongsheng (Frontiers in Microbiology, 2016)
Pandemic Vibrio parahaemolyticus is an emerging public health concern as it has caused numerous gastroenteritis outbreaks worldwide. Currently, the absence of a global overview of the phenotypic and molecular characteristics of pandemic strains restricts our overall understanding of these strains, especially for environmental strains. To generate a global picture of the sero-prevalence and genetic diversity of pandemic V. parahaemolyticus, pandemic isolates from worldwide collections were selected and analyzed in this study. After a thorough analysis, we found that the pandemic isolates represented 49 serotypes, which are widely distributed in 22 countries across four continents (Asia, Europe, America and Africa). All of these serotypes were detected in clinical isolates but only nine in environmental isolates. O3:K6 was the most widely disseminated serotype, followed by O3:KUT, while the others were largely restricted to certain countries. The countries with the most abundant pandemic serotypes were China (26 serotypes), India (24 serotypes), Thailand (15 serotypes) and Vietnam (10 serotypes). Based on MLST analysis, 14 sequence types (STs) were identified among the pandemic strains, nine of which fell within clonal complex (CC) 3. ST3 and ST305 were the only two STs that have been reported in environmental pandemic strains. Pandemic ST3 has caused a wide range of infections in as many as 16 countries. Substantial serotypic diversity was mainly observed among isolates within pandemic ST3, including as many as 12 combinations of O/K serotypes. At the allele level, the dtdS and pntA, two loci that perfectly conserved in CC3, displayed a degree of polymorphism in some pandemic strains. In conclusion, we provide a comprehensive understanding of sero-prevalence and genetic differentiation of clinical and environmental pandemic isolates collected from around the world. Although, further studies are needed to delineate the specific mechanisms by which the pandemic strains evolve and spread, the findings in this study are helpful when seeking countermeasures to reduce the spread of V. parahaemolyticus in endemic areas.